IDENTIFIKASI RISIKO PADA PELAKSANAAN PEMBANGUNAN DENPASAR SEWERAGE DEVELOPMENT PROJECT (DSDP) DI DENPASAR - Oka Suputra, I Gusti Ngurah; Norken, I Nyoman; Adnyana Putera, I Gusti Agung (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 2 Juli 2005, 2012)
Waste water which is produced by population of Denpasar City has not been managed properly, therefore it will potentially contaminate the environment. In order to solve this problem, the Government of Denpasar City has been granted loan by the Japan Bank for International Corporation (JBIC), and has been use for the development of sewerage system called Denpasar Sewerage Development Project (DSDP). During construction phase that has been executed, variety of risk was found which is potentially obstruct project implementation, and even cancel part of the project. The study is presented to identify risk comprehensively, through brain storming and structured interviews. As result, the risk have been identified 74 (seventy four) risk, which include risk souces of 5 (6,76%) unacceptable risk, 17 (22,97%) undesirable risk, 22 (29,73%) acceptable risk, and 30 (40,54%) negligible risk.Unacceptable and undesirable risk which considered as major risk come from political risk 1 risk (4,65%), environmental risk 6 risk (27,27%), planning risk 1 risk (4,55%), economical risk 1 risk (4,55%), financial risk 1 risk (4,55%), project risk 8 risk (36,36%), technical risk 2 risk (9,09%), and others 2 risk (9,09%) are include on human risk. The results show that risk sources of environmental and project risk are dominant, and should be handled specially by the stakeholder who responsible to this project.
Keywords: risk, risk identification, comprehensive